PENDAMPINGAN BRANDING DAN KONTEN PEMASARAN DIGITAL KAMPUNG WISATA BINONG BERBASIS PARTICIPATORY ACTION RESEARCH - Daniel Hermawan (Jurnal Abdimas Bina Bangsa, 2023)
Binong Tourism Urban Village’s assistance is a community service program with the MBKM Village Project scheme managed by the Business Administration Study Program, Faculty of Social and Political Sciences, Parahyangan Catholic University. In line with the Certificate of Confirmation of the Tourism Awareness Group (Pokdarwis) No. 46/SK/BNG/VI/2022 from the Binong Urban Village, as well as the priority issues disclosed by Eka Rahmat Jaya as the Chairperson of the Binong Urban Village Pokdarwis, branding and digital marketing content are the 2 main issues that are followed up in the 2022/2023 Odd Semester MBKM Village Project. As an integrated part of the tourism awareness movement, mentoring is expected to foster the love and pride of the Binong Urban Village community, as well as increase community brand awareness of Binong Tourism Urban Village, both internally and externally. Assistance was carried out with MBKM students using the participatory action research method for Pokdarwis members of the Binong Urban Village, starting from knowing, understanding, planning, action, and reflecting. Through this assistance, Pokdarwis members of the Binong Urban Village will gain increased knowledge and skills related to branding and digital marketing content